A novel universal adhesive for improved dentin remineralization with antibiofilm potential against Streptococcus mutans and other cariogenic-pathogens. (October 2022) - Mi, Changjiang; Jing, Zhixing; Zhu, Wanchun
Abstract: Dental demineralization is a widespread problem and the main responsible for dental caries and dentin hypersensitivity. Dental caries is a biofilm-driven bacterial infection that causes mineral depletion in enamel and is associated with an increased prevalence of medical rehabilitative polymeric implants. Since existing tissue-engineering methods are incapable of manufacturing synthetic dentin adhesive, modern therapeutic interventions address the remineralization of caries-infected dentin to prevent its inevitable removal. In recent years, magnetic nanoparticle-coated adhesives were known to deliver drugs to the pulp and get better adhesive penetration into dentin. In the present study, we prepared and assessed the effectiveness of antimicrobial peptide (cecropin A) coated Fe3 O4 -nanoparticle on dentin remineralization, bond strength, and its antibiofilm potential against Streptococcus mutans, is associated with dental caries in humans. Prior to the experiment, the synthesized cecropin@Fe3 O4 nanoparticle was characterized and assessed its antibiofilm potential against S. mutans . The transcriptomic approach with qPCR analysis stated that cecropin@Fe3 O4 nanoparticle significantly downregulated the expression of biofilm-regulated genes such as GtfB, GtfC, GtfD, VicR, ComDE, and Smu0630 in S. mutans, which validates the outcome of in vitro results. Interestingly, the prepared cecropin@Fe3 O4 -nanoparticle coated adhesive effectively increased the dentin remineralization and bond strength. Fascinatingly, cecropin@Fe3 O4 adhesive significantly hindered the biofilm formation of S. mutans on the dentin surface. Notably, the cecropin@Fe3 O4 adhesive accomplished reduced biofilm CFU count, lactic acid production, and biofilm metabolic activity. In addition, the cecropin@Fe3 O4 adhesive also reduced the biofilm formation of other caries-associated bacterial pathogens, including S. sobrinus, S. sanguinis, and S. mitis . Overall, the current research found that the cecropin@Fe3 O4 adhesive was more effective in remineralizing dentin lesions with antibiofilm potential in order to avoid Streptococcus -derived dental caries. Graphical abstract: Image 1 Highlights: Cecropin-A coated Fe3 O4 -nanoparticles exhibited effective antibiofilm and antivirulence activity against Streptococcus mutans. Cecropin@Fe3 O4 -nanoparticles downregulated the expression level biofilm-related genes. cecropin@Fe3 O4 -nanoparticles incorporated universal-adhesive showed improved dentin remineralization and bond strength. Cecropin@Fe3 O4 adhesive achieved reduced biofilm, lactic acid production, and their metabolic activity of S. mutans. In addition, cecropin@Fe3 O4 adhesive has potent antibiofilm activity against S. sobrinus, S. sanguinis, and S. mitis.